Republic of Kazakhstan : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper reviews the developments, issues, and prospects of the petroleum sector of Kazakhstan, and analyzes the recent strong economic growth, the links between the oil and the non-oil sector, and assesses the contribution of each sector. It explores the trade policy options facing Kazakhstan, and describes the latest developments in the banking sector, insurance, pension funds, capital markets, pension system, and unified financial sector supervision. It also provides a statistical appendix highlighting the IMF's projections and estimates of the Republic of Kazakhstan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet